Gróf Zichy Béla hitbizományi uradalmának fejlődése (1887-1914) - Kaposi, Zoltán (Közép-Európai Közlemények, 2024)
The study deals with the economic development of the entailed manor of Lengyeltóti owned by Count Béla Zichy. According to the current literature entailed estates were running with low efficiency. However, based on my preliminary findings it appears that there were a few innovative entailed large-scale agricultural plants in Somogy County. The main question is whether it was possible to implement modernisation within the legal framework of an entail. I have used archival sources, statistics, press sources, literature and genealogic sources. I have established that the Manor of Lengyeltóti successfully dealt with all the external economic hardships (decrease in crop prices and wine blight). It implemented many innovations and through its initiations it contributed to the national agricultural development. The manor enjoyed successes in the field of intensive livestock farming and growing animal fodder plants and industrial crops. Its significant achievements included converting water-meadows to lands, engaging in railway development and the large-scale peat extraction within the industrial system of the manor. Its initiative participation in the tourism of Lake Balaton still has its effects felt today. This obviously required an owner with broad vision and proper management. Our study shows that not the legal category of the estate (entailed of free) was the decisive factor; in the ages of capitalism an owner of an entail could became a successful agriculture entrepreneur.